Law, Comparatism, and Epistemic Governance: There Is Critique and Critique. Issue 3 (1st May 2017) - Glanert, Simone; Legrand, Pierre
Abstract : How many scholarly fields have experienced the disappointing fate of comparative law and continued in the grip of a demonstrably indigent epistemology for decades on end? After the early postmodernity witnessed their protracted servitude to Les Grands systèmes's jejune classifications, facile correspondences, and meagre interpretive return — a predicament which, implausibly, endures in countries as diverse as Brazil, France, and Russia — law's comparatists began taking their epistemic orders from Hamburg and the Hamburgher diaspora. For fifty years or so, they have been gorged on a diet of Rechtsdogmatik, scientism, objectivity, neutrality, truth, and assorted shibboleths. As if these epistemic delusions were not problematic enough, the earlier, obsolete model was eventually revived although tweaked to focus on traditions instead of systems (or families). While critics were occasionally moved to chastise threadbare Hanseatic knowledge-claims — some expressing their concern in conspicuous venues, others harnessing prestigious institutional affiliations — comparative law's orthodoxy, somewhat extraordinarily, has hitherto been able to operate unencumbered by any epistemic challenge whose monographic exposition would have proved decidedly pre-eminent. It is the great merit of Gunter Frankenberg's Comparative Law As Critique, in crucial respects an account at once capital and extensive, that it interrupts, finally, the longstanding deployment of comparative law's mainstream imposture. Frankenberg's refutation is thus well worth restating, and the first part of this review wishes loyally to apply itself to this important representative task not least by affording the author much latitude to express himself in his own voice. Yet, Frankenberg's considerable critical integrity notwithstanding, this essay holds that his epistemic transgression remains too diffident. Specifically, five key concerns at least warranted more subversive epistemic commitments than Frankenberg allows. In the wake of Comparative Law As Critique, the second part of this commentary addresses these contentions with a view to making a case both for comparative law as strong critique and for the paradigmatic epistemic turn that has been persistently deferred within the field.